Creutzfeldt-Jacob Illness and Other Prion Diseases (Review) - José L Colina B; Gabriela Blanchard (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2003)
Creutzfeldt-Jakob disease (ECJ) is a sub-acute human encephalopathy and progressive associated with a degeneration central nervous system spongiform (SNC). The ECJ belongs to the encephalopathies group transmissible spongiform with an aberrant protein metabolism prions (PrP). Its pathophysiological mechanism exact is still not known clearly but It is thought that this neurodegeneration is related to protein accumulation altered prionics (5, 13, 14, 24, 37). The protein of prions originally identified in rodents infected with Scrapie, it is encoded for a single copy chromosomal gene, this gene is highly conserved and has been identified in more than 13 species of mammals It is usually composed by two exons not translated into 5 separate for a 2 Kb intron. The prevailing uncertainty about PrP and its conformational malleability I dictate the search for linked genes and regulatory elements that could play an active role, but to date it has not been possible to identify any gene related (molecular carbines, etc.), but if some characteristics have been observed not expected within wild genes of PrP.